CALCULATION METHOD OF MILLING PEAT THERMOCHEMICAL PROCESSING IN THE FLOW OF GAS HEAT CARRIER - Воробйов, Леонід; Скляренко, Євген (Modern engineering and innovative technologies, 2022)
The prospects for the use of milled peat by its preliminary thermochemical processing are considered. The technological scheme of the process of thermochemical processing of milled peat in the flow of high-temperature gas coolant, the main aspects of oper